Bilateral congenital ureteral strictures in a young cat - Lee, Namsoon (Canadian Veterinary Medical Association, 2014)
An 8-month-old cat was presented with bilateral hydronephrosis. Bilateral ureteral obstructions were identified by diagnostic imaging and confirmed by necropsy. Histopathologic findings revealed polypoid transitional epithelial hyperplasia with chronic lymphoplasmacytic inflammation. This report documents congenital ureteral strictures as a cause of ureteral obstruction in a young cat.